Sumber Belajar Biologi Berupa Majalah Pada Materi Jamur Untuk Siswa Sekolah Menengah Atas - Alfin ipin (EDU-BIO: Jurnal Pendidikan Biologi, 2018)
The objectives of this study is to develop learning resources in the form of Biology magazines on mushroom material for sudents of senior high school 3 Muara Bungo with valid categories. The type of this Research is Research and Devlopment. The model of Development used was four-D model which consists of define, design, and development. In the define stage conducted curriculum analysis , student analysis, task analysis, concept analysis. Design stage conducted by designing Biology magazine. Furthermore, in the development stage conducted expert validation, test of ten grade students MIA I and MIA II at senior high school 3 Muara Bungo. The research data of feasibility test was obtained by questionnaire of student’s response. The results of this study was questionnaire responses of then grade students MIA I and MIA II and has beech declared eligible with the pncentage of students who stated strongly agree with the magazine developed were 3,43%, students who agree were 7,84%, students who disagree were 0,5%, and students who strongly disagree were 0,21% based on theresults conducted it can be concluded Biology magazine on mushroom material for senior high school studnts were elegible to use.Keywords: Magazine, Mushroom, Four-D, Student